Natural Selfing in Bambusa bambos (l.) Voss, Besch. (syn. Bambusa arulvdinacea (retz.) Willd as Estimated from Albino Frequencies - Kumar, Adarsh; Sharma, V. K.; Dhiman, R. C. (Indian Forester, 1995)
No abstract